2010
DOI: 10.1080/09500341003624743
|View full text |Cite
|
Sign up to set email alerts
|

High resolution reflection tomographic diffractive microscopy

Abstract: International audienceWe have developped a tomographic diffractive microscope in reflection, using a high numerical aperture objec- tive and equipped with a fluorescence confocal scanner. We describe the set-up and first images of a microscopic USAF target, obtained in holographic, diffractive tomographic, and confocal mode, and which reveal the higher resolution capabilities of this instrument. We also compare images obtained in transmission and in reflection, emphasizing the better optical sectionning capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…The set of recorded frequencies in reflection TDM depicts a portion of a filled sphere, with the same lateral extension than that obtained in transmission TDM, but now comprising high frequencies along the optical axis, see Figure 9(c). From this construction, one therefore predicts that reflection TDM should be characterized by superior sectioning capabilities along the optical axis, which has been recently experimentally demonstrated [51]. Note that reflection configurations have often been used to study 2-D or quasi 2-D objects [7,[52][53][54] under paraxial approximation (which corresponds to low numerical aperture), see Eq.…”
Section: Tomography With Illumination Rotation In Reflectionmentioning
confidence: 99%
“…The set of recorded frequencies in reflection TDM depicts a portion of a filled sphere, with the same lateral extension than that obtained in transmission TDM, but now comprising high frequencies along the optical axis, see Figure 9(c). From this construction, one therefore predicts that reflection TDM should be characterized by superior sectioning capabilities along the optical axis, which has been recently experimentally demonstrated [51]. Note that reflection configurations have often been used to study 2-D or quasi 2-D objects [7,[52][53][54] under paraxial approximation (which corresponds to low numerical aperture), see Eq.…”
Section: Tomography With Illumination Rotation In Reflectionmentioning
confidence: 99%
“…In a different work, it has also been recently shown that reflection tomographic diffractive microscopy permits a longitudinal resolution at least comparable to a reflection confocal microscope [14]. The successful combination of transmission and reflection diffractive tomography in a two-objective microscope [2] is still to be performed, but would open the way to microscopy of unlabelled specimen with a 3D isotropic resolution in the 100 nm range, which would represent a real breakthrough for microbiology.…”
Section: Resultsmentioning
confidence: 97%
“…[10][11][12][13][14] However, a drawback of many experimental arrangements 1,2,[4][5][6][7][9][10][11][12][13] is the requirement for a separate reference wave, which results in a phase stability decrease and the demand for a precise adjustment of the intensity ratio between object and reference wave. To overcome these problems several approaches were reported.…”
Section: Introductionmentioning
confidence: 99%